GERAKAN AKSI SOSIAL SEBAGAI WUJUD KEPEDULIAN BERSAMA MELALUI KEGIATAN BERBAGI SEMBAKO DAN BANTUAN TUNAI DESA TROPODO, KECAMATAN WARU - Samsul Arifin; Ullkhissyah Syarifah Sendy; Didit Darmawan; Rahayu Mardikaningsih; Mila Hariani (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This Community Service (PkM) activity was carried out as an effort to foster social awareness. The background to this activity was related to population density, high unemployment rates, and the large number of elderly residents who were no longer economically active. The method used in this activity was the SWOT approach based on Asset Based Community Development (ABCD), which focuses on utilizing the strengths and local resources of the community. The implementation of this activity included collecting data on residents who needed assistance, distributing basic necessities and financial support, and interacting directly with the community. The results of this activity show that the assistance provided can reduce the burden of basic needs on the community and also increase empathy, social awareness, and a spirit of mutual cooperation. This activity also teaches the younger generation to be more sensitive and responsible towards social issues around them. Overall, this PKM initiative is expected to have a positive and sustainable social impact on the Tropodo Village community.